LAMA5: A new pathogenic gene for non-syndromic cleft lip with or without cleft palate - Zhenzhen Fu; Yan Qi; Ling-fa Xue; Yao-xiang Xu; Jin Yue; Jin-ze Zhao; Cong Li; Wenlin Xiao (Biomedical Journal, 2024)
Background: This study aimed to investigate the effect of LAMA5 on palatal development in mice. Methods: The palatine process of C57BL/6 J fetal mice on the embryonic day 13.5 (E13.5) was cultured in vitro via the rotating culture method. The LAMA5-shRNA adenovirus vector was constructed, then transfected into the palatal process of E13.5 for 48 h in vitro. A fluorescence microscope was used to visualize the fusion of palates. The expression of LAMA5 was also detected. The expression of ki67, cyclin D1, caspase 3, E-cadherin, vimentin and SHH signaling pathway-related signaling factors in the blank control group, the negative control group, and the LAMA5 interference group were detected after virus transfection. Results: The bilateral palates in the LAMA5 interference group were not fused after virus transfection. PCR and WB showed that the mRNA and protein expressions of LAMA5 were decreased in the LAMA5 interference group. Furthermore, the mRNA and protein expressions of ki67, cyclin D1 and gli1 were decreased in the LAMA5 interference group, while the mRNA and protein expressions of caspase 3 were increased. However, the mRNA and protein expression of E-cadherin, vimentin, Shh and ptch1 did not significantly change in the LAMA5 interference group. Conclusions: LAMA5 silencing causes cleft palate by inhibiting the proliferation of mouse palatal cells and promoting apoptosis, which may not be involved in EMT. LAMA5 silencing can also cause cleft palate by interfering with the SHH signaling pathway.